Decreased Benzodiazepine Receptor Binding in Prefrontal Cortex in Combat-Related Posttraumatic Stress Disorder - Bremner, J. Douglas; Innis, Robert B.; Southwick, Steven M.; Staib, Lawrence; Zoghbi, Sami; Charney, Dennis S. (The American journal of psychiatry, 2000)
OBJECTIVE: Animals exposed to stress exhibit a decrease in benzodiazepine receptor binding in the frontal cortex. No studies have examined central benzodiazepine receptor binding in patients with posttraumatic stress disorder (PTSD). The purpose of this study was to examine measures of benzodiazepine receptor binding in PTSD.METHOD: From 13 patients with Vietnam combat-related PTSD and 13 case-matched healthy comparison subjects, a quantitative measure related to benzodiazepine receptor binding (distribution volume) was obtained with single photon emission computed tomography (SPECT) imaging of [123I]iomazenil binding and measurement of radioligand concentration in plasma. Distribution volume image data were analyzed by means of statistical parametric mapping.RESULTS: Lower distribution volumes were found in the prefrontal cortex (Brodmann's area 9) of PTSD patients than in comparison subjects.CONCLUSIONS: These findings of lower values for the benzodiazepine receptor binding measure of distribution volume are consistent with fewer benzodiazepine receptors and or reduced affinity of receptor binding in the medial prefrontal cortex in patients with PTSD. Alterations in benzodiazepine receptor function in this area may underlie many of the symptoms of PTSD.